Effects of feedback on residential electricity demand: Findings from a field trial in Austria - Joachim Schleich; Marian Klobasa; Sebastian Götz; Marc Brunner (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2012)
This paper analyzes the effects of providing feedback on electricity consumption in a field trial involving more than 1,500 households in Linz, Austria. About half of these households received feedback together with information about electricity-saving measures (pilot group), while the remaining households served as a control group. Participation in the pilot group was random, but households were able to choose between two types of feedback: access to a web portal or written feedback by post. Results from cross section OLS regression suggest that feedback provided to the pilot group corresponds with electricity savings of around 4.5 % for the average household. Our results from quantile regressions imply that for house-holds in the 30th to the 70th percentile, feedback on electricity consumption is statistically significant and effects are highest in absolute terms and as a share of electricity consumption. For percentiles below or above this range, feedback ap-pears to have no effect. Finally, controlling for a potential endogeneity bias induced by non random participation in the feedback type groups, we find no difference in the effects of feedback provided via the web portal and by post.
urn:nbn:de:0011-n-2196713
Keywords: 330; smart metering; feedback; household electricity consumption; Messgerät; Elektrizität; Energiekonsum; Privater Haushalt; Energiesparen; Österreich